PENGARUH AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN SERTA MOTIVASI TERHADAP KINERJA GURU DI SMAN 1 DAN SMAN 68 JAKARTA PUSAT - Hadijah Sanadi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2019)
This study aims to understand accountability and improve financial management as well as partial and simultaneous motivation for teacher performance in SMAN 1 dan SMAN 68 Jakarta. The research approach is a quantitative and associative quantitative approach. Data obtained using a questionnaire. The population is 82 teachers of SMAN 1 and SMAN 68, Central Jakarta, using saturated sample techniques. Data analysis technique is statistical analysis of multiple linear regression. The results of the study, partially the accountability variable has a positive effect on teacher performance. Transparency variable does not significantly influence teacher performance. The motivation variable partially has a significant effect on performance. Simultaneously the accountability, transparency and motivation variables significantly influence teacher performance. The ability of accountability, transparency, and motivation to explain changes in teacher performance is 58.4%. Among the three variables that most dominant influence teacher performance is motivation, thus motivation is very helpful for teachers in improving their performance.